High loft sea island - high shrinkage polyester composite filament and method of making same

CN122039289BActive Publication Date: 2026-10-27HANGZHOU XULONG CLOTH MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610210844.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-13
Publication Date
2026-10-27
Estimated Expiration
2046-02-13

AI Technical Summary

Technical Problem

然而,上述方案普遍存在以下共性问题:其一,采用单一COPET海相时,为实现充分开纤往往需要较高浓度碱液和较长处理时间,容易造成PET岛丝强力下降和疲劳性能劣化,同时碱耗和废水处理成本较高;其二,采用单一PVA海相时,虽然可以利用热水溶解海相减轻碱污染,但海相完全溶除后,超细岛丝束缺乏额外“骨架”支撑,织物在高蓬松与长期压缩回复性之间难以平衡

Benefits of technology

[0027]本发明通过在海岛型涤纶中引入水溶性PVA与碱溶性COPET组成的双海相,并将其与高收缩共聚涤纶长丝复合,利用“热水、轻碱”的分段处理过程,实现对海相空间分布的可控重构:在90~98℃热水处理中,PVA优先溶解,海相内部形成贯通孔道和界面空隙,保留的COPET仍维持海岛整体结构;随后在1~5g/L低浓度NaOH溶液中仅部分溶解COPET,使其由连续相退化为局部残留,因相容性与表面能差异,残留COPET热力学上更易富集于与高收缩组分长丝接触的周向界面区域,最终在纤维横截面形成“超细PET岛丝、高收缩涤纶长丝、靠近高收缩长丝周向分布的COPET残留包覆层”的复合微观骨架结构,在后续热收缩与使用过程中,该骨架单元协同变形并对岛丝束起到缓冲、锚固和载荷分散作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

The application discloses a kind of high-bulk island-high shrinkage polyester composite filament and preparation method thereof.The composite filament is formed by island component filament and high shrinkage component filament, and the island component filament is formed by water-soluble PVA and alkali-soluble COPET, and PET forms island phase;The high shrinkage component filament is copolymer polyester filament.The preparation method comprises: island POY, high shrinkage polyester filament, parallel stretching, heat setting and air interlacing into a bundle, and then sequentially performing hot water treatment and mild alkali reduction of low concentration sodium hydroxide solution, so that PVA is dissolved and removed, COPET is partially dissolved and mainly remains in the circumference of high shrinkage filament.The structure reduces the strength of alkali reduction and environmental burden, realizes the superfine of island filament and the stability of composite skeleton, and improves the bulkiness and compression recovery performance of suede, imitated wool and high-bulk filling material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical fiber technology, and particularly relates to a high-loft island-high shrinkage polyester composite filament and its preparation method. Background Technology

[0002] The demand for microfiber and high-loft fabrics, such as those mimicking suede and wool, has been steadily increasing in recent years in the apparel, home textiles, and automotive interiors sectors. A typical manufacturing process involves using island-type polyester fibers. The marine phase is dissolved to remove the microfiber, resulting in ultrafine island fibers with a single filament fineness of 0.01–0.1 dtex. These are then compounded or blended with high-shrinkage polyester filaments, followed by weaving, weight reduction opening, and finishing to obtain fabrics that are both soft and delicate, yet also fluffy and crisp. In island-type fibers, the "islands" are PET or other polymers providing the mechanical framework, while the "sea" consists of copolyesters such as COPET, water-soluble polyesters, or polyvinyl alcohol (PVA) that are soluble in alkaline solutions or hot water. The fiber opening method and weight reduction conditions directly affect the strength retention rate of the microfiber, the fabric's resilience, and its environmental impact.

[0003] Chinese patent CN100595358C discloses a method for manufacturing wool-like polyester composite filaments. The method involves stretching and false-twisting polyester island-type POY with conventional polyester POY to form a blended filament containing a single filament fineness of less than 0.1 dpf and a boiling water shrinkage rate of less than 6%. This blended filament is then combined with high-shrinkage polyester FDY (boiling water shrinkage rate greater than 20%) at the network nozzle. The resulting fabric is then woven and subjected to alkali reduction and fiber opening to obtain the wool-like polyester composite filament fabric. The weight reduction processing conditions are: NaOH solution concentration of 15%–25%, treated at 100℃ for 30–60 minutes, so that the island component in the island-type filament is almost completely dissolved, and the ultrafine island filaments are fully exposed. This method can obtain wool-like fabrics with a soft hand feel and good resilience, but it suffers from the problems of high alkali concentration and long processing time, which can easily cause hydrolytic damage to the PET island filaments. Furthermore, the high concentration of alkali and the wastewater treatment pose significant environmental pressure.

[0004] Another patent, CN103122502A, proposes a PET / COPET island-type copolyester composite fiber. The island component is COPET, a water-soluble polyester, and the island component is copolymerized PET modified with branched aliphatic diols. The sea / island mass ratio is 20–40 wt% : 80–60 wt%. This paper describes how to dissolve the sea component COPET in a 1–3 wt% NaOH solution within 40–60 minutes to obtain a low-temperature dyeable modified PET microfiber fabric, which improves dyeing performance and hand feel. However, its technical approach is still to dissolve the sea component as completely as possible, aiming to obtain "clean" single-component microfiber island yarns, without considering retaining some sea phase to construct a three-dimensional skeleton or a synergistic bulking structure with the high-shrinkage component.

[0005] In existing technologies, for applications such as suede and imitation wool, island-type microfiber polyester is typically composited or blended with high-shrinkage polyester filaments. The high-shrinkage fibers' thermal shrinkage and the thick coverage of the microfibers create a fluffy appearance and soft touch. However, these solutions generally suffer from the following common problems: First, when using a single COPET sea phase, achieving full fiber opening often requires a high concentration of alkali solution and a long treatment time, easily leading to a decrease in the strength of the PET island filaments and deterioration in fatigue performance. Simultaneously, alkali consumption and wastewater treatment costs are high. Second, when using a single PVA sea phase, although hot water can be used to dissolve the sea phase and reduce alkali contamination, once the sea phase is completely dissolved, the microfiber bundles lack additional "skeleton" support, making it difficult to balance high bulkiness with long-term compression recovery.

[0006] Furthermore, in the study of weight reduction and fiber opening of COPET / PET island fibers, most literature optimizes the process from the perspective of the influence of NaOH concentration, temperature, and time on the weight reduction rate and dyeability. The goal is still to improve the dissolution efficiency of the sea component and the uniformity of weight reduction. However, it does not combine the synergistic design of high-shrinkage copolymer polyester on the bulk elasticity and cyclic compression recovery of the fiber bundle, nor does it have a structural control approach to build a stable volume skeleton.

[0007] Therefore, existing technologies lack a solution that can simultaneously reduce alkali reduction strength, mitigate adverse effects on PET island yarns and the environment, achieve ultra-fine island yarns while maintaining strength, and improve the thickness recovery and long-term durability of high-loft fabrics after multiple compressions. Summary of the Invention

[0008] The purpose of this invention is to provide a high-loft island-high-shrinkage polyester composite filament using PVA / COPET dual marine phase and combined with high-shrinkage polyester, and its preparation method. Under the premise of reducing alkali reduction strength and mitigating the adverse effects on PET island filaments and the environment, the island filaments are made ultra-fine and a stable volume skeleton is constructed, thereby significantly improving the loft and compression recovery of fabrics such as imitation suede and imitation wool.

[0009] To achieve the above-mentioned technical objectives, the present invention provides the following technical solution.

[0010] In a first aspect, the present invention discloses a high-loft island-sea-high-shrinkage polyester composite filament, which is composed of an island-sea component filament and a high-shrinkage component filament:

[0011] The island-type filament is an island-type polyester filament, the sea phase is water-soluble PVA and alkali-soluble COPET, the mass ratio of PVA to COPET is (30-60):(70-40); the island phase is PET.

[0012] The high-shrinkage component filament is a copolyester filament with a shrinkage rate of 35-55% in boiling water at 100°C.

[0013] The linear density ratio of the island component filament to the high-shrinkage component filament is (40-70):(60-30). The composite filament is subjected to hot water treatment at 90-98℃ and alkaline reduction treatment with 1-5g / L sodium hydroxide aqueous solution to dissolve and remove PVA in the marine phase and partially dissolve COPET. The linear density of the PET island phase monofilament in the resulting composite filament is 0.03-0.10dtex, and the residual COPET is mainly distributed in the circumferential coating area close to the high-shrinkage component filament.

[0014] Preferably, the mass ratio of marine phase to island phase in the island component filament is (25-40):(75-60), and the number of islands in the PET island phase monofilament is 24-64.

[0015] Preferably, the PVA has a saponification degree of 88-99% and a number-average degree of polymerization of 800-2000.

[0016] Preferably, the COPET is copolymerized from terephthalic acid, ethylene glycol, and aromatic dicarboxylic acid containing sulfonate hydrophilic groups, and its glass transition temperature is 10-30°C lower than that of PET.

[0017] Preferably, the high-shrinkage component filament copolyester is obtained by copolymerizing terephthalic acid, isophthalic acid and ethylene glycol, wherein the molar fraction of isophthalic acid is 8-18%.

[0018] In a second aspect, the present invention discloses a method for preparing the high-loft island-sea-high-shrinkage polyester composite filament described in the first aspect, comprising:

[0019] S1, PVA and COPET are melt-blended to obtain a dual marine phase melt, which is then spun into a sea-island type composite melt in the same spinneret as the PET melt to obtain a sea-island type pre-oriented yarn POY with PVA / COPET as the marine phase and PET as the island phase;

[0020] S2, prepare copolyester and perform melt spinning and drawing to obtain high shrinkage component filament with a shrinkage rate of 35-55% in boiling water at 100℃;

[0021] S3, the island-type pre-oriented yarn and the high-shrinkage component filament are fed into the drawing and heat-setting device in parallel at a linear density ratio of (40-70):(60-30), drawn at a total drawing ratio of 1.6-2.5, and heat-set in a hot box at 140-190°C. At the same time, they are bundled together through an air network nozzle to obtain composite filament.

[0022] S4. The composite filament is treated in hot water at 90-98°C for 1-10 minutes to dissolve and remove PVA from the marine phase, and then treated in a 1-5 g / L sodium hydroxide aqueous solution for 5-20 minutes to partially dissolve COPET from the marine phase. It is then washed with water and subjected to relaxation heat treatment.

[0023] Preferably, in step S1, the spinning temperature of the island-type POY is 260–290°C, the cooling air temperature is 18–24°C, the winding speed is 2500–3500 m / min, and the viscosity ratio of the marine melt to the island melt is 0.8–1.2.

[0024] Preferably, in step S3, the overfeed rate of the high-shrinkage component filament relative to the island component filament is 5-15%, the air pressure of the air network nozzle is 0.2-0.5 MPa, and the interlacing density of the resulting composite filament is 15-35 nodes / m.

[0025] Preferably, the mass reduction of the composite filament after the hot water treatment in step S4 is 8-18%, and the total mass reduction of the composite filament after the alkali reduction treatment is 15-25%.

[0026] Thirdly, the present invention discloses the use of the high-loft island-high-shrinkage polyester composite filament described in the first aspect for preparing suede, imitation wool or high-loft filling materials.

[0027] This invention introduces a dual marine phase composed of water-soluble PVA and alkali-soluble COPET into island-type polyester, and then composites it with high-shrinkage copolymer polyester filaments. Utilizing a segmented treatment process of "hot water and light alkali," the spatial distribution of the marine phase is controllably reconstructed: In hot water treatment at 90–98°C, PVA preferentially dissolves, forming interconnected channels and interfacial voids within the marine phase, while the retained COPET maintains the overall island structure; subsequently, in a low-concentration NaOH solution of 1–5 g / L, only the COPET is partially dissolved, causing it to degenerate from a continuous phase to a localized residue. Due to differences in compatibility and surface energy, the residual COPET is thermodynamically more likely to accumulate in the circumferential interfacial region in contact with the high-shrinkage component filaments. Ultimately, a composite micro-skeleton structure is formed in the fiber cross-section consisting of "ultra-fine PET island filaments, high-shrinkage polyester filaments, and a COPET residue coating layer distributed circumferentially near the high-shrinkage filaments." During subsequent heat shrinkage and use, this skeleton unit deforms synergistically and acts as a buffer, anchor, and load-dispersing element for the island filament bundles.

[0028] The beneficial technical effects achieved by this invention are as follows: By utilizing the above-mentioned dual-ocean-phase and segmented dissolution structural design, this invention achieves stable ultrafine PET island filaments and strong strength retention while significantly reducing alkali reduction concentration and treatment intensity, thus mitigating the hydrolytic damage to fibers caused by strong alkali and the environmental burden. Simultaneously, the residual COPET forming a circumferential coating skeleton in the high-shrinkage filaments allows the composite filaments to maintain good three-dimensional support and recovery capabilities under the shrinkage of high-shrinkage fibers and external compression. This results in suede, imitation wool, and high-loft filling materials made from these composite filaments exhibiting higher initial loft, better compression recovery, and thickness retention during long-term use, even with a reduced unit area mass. Compared to existing technologies using a single COPET or PVA ocean phase combined with conventional high-shrinkage polyester, the overall performance and service life are significantly improved. Detailed Implementation

[0029] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. It should be understood that the described embodiments are only some embodiments of the present invention, and not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort all fall within the protection scope of the present invention.

[0030] I. Terminology and Raw Material Description

[0031] To facilitate understanding of this invention, some of the terms and materials used in this specification will be explained first.

[0032] 1. Island-type polyester filament

[0033] In this specification, "island-type polyester filament" refers to a type of composite fiber in which the island phase appears as multiple dispersed small regions on the fiber cross-section, and the sea phase forms a continuous phase that coats the outside of the island phase or fills the spaces between the island phases. The island phase is retained after subsequent processing to form ultrafine filaments, while the sea phase is a polymer that can be selectively dissolved and removed. In this invention, the island phase is PET, and the sea phase is a dual-sea phase system of water-soluble PVA and alkali-soluble COPET.

[0034] 2. PVA

[0035] PVA is polyvinyl acetate that has undergone saponification and has a certain degree of water solubility. This invention preferably uses PVA with a saponification degree of 88-99% and a number-average degree of polymerization of 800-2000, so that it can be fully dissolved in hot water at 90-98°C within 1-10 minutes to achieve the first stage of water-soluble fiber opening.

[0036] 3. COPET

[0037] The alkali-soluble COPET described in this invention refers to a polyester obtained by copolymerizing PTA and ethylene glycol (EG) with aromatic dicarboxylic acid monomers containing sulfonate hydrophilic groups (such as sodium 5-sulfonic acid isophthalate). Alkali-soluble COPET chains contain ionic hydrophilic groups, resulting in a lower glass transition temperature compared to PET. Preferably, the glass transition temperature of COPET is 10–30°C lower than that of PET. Furthermore, it readily expands, breaks down, and dissolves under weakly alkaline conditions, exhibiting a high dissolution rate and facilitating selective dissolution at low NaOH concentrations.

[0038] 4. High-shrinkage copolyester

[0039] The high-shrinkage component filament in this invention is a copolyester filament. Preferably, a PTA / IPA / EG ternary system is used, wherein isophthalic acid (IPA) accounts for 8-18% of the total molar amount of the diacids. By controlling the copolymerization ratio and drawing conditions, the high-shrinkage filament achieves a shrinkage rate of 35-55% in boiling water at 100°C and a shrinkage rate of 20-35% in dry heat at 180°C.

[0040] In the preferred embodiments 1 and 2, the high-shrinkage copolyester is copolymerized only from PTA, IPA and EG, and contains little or no sulfonate hydrophilic groups. Its crystallinity and hydrophobicity are close to those of ordinary PET. Under the above-mentioned weakly alkaline conditions, only slight surface hydrolysis occurs, and its mass reduction does not exceed 2% of the original mass. There will be no overall dissolution or significant decrease in mechanical properties.

[0041] In optional Example 3, a small amount of aromatic dicarboxylic acid monomers containing sulfonate hydrophilic groups (such as 5-sulfonic acid isophthalic acid metal salt) are introduced into the PTA / IPA / EG system to improve the dyeability and hydrophilicity of high-shrinkage filaments without significantly weakening their alkali resistance.

[0042] 5. Quality reduction rate

[0043] In this invention, the degree of marine phase dissolution is characterized by the mass loss rate. The mass loss rate R is calculated using the following formula:

[0044]

[0045] in, The drying quality before the reduction. The drying quality after weight reduction treatment.

[0046] 6. Density of intersecting nodes

[0047] Interlocking density refers to the number of interlocking points formed by the air network on a unit length of filament, measured in "interlocking points / m". By adjusting the air nozzle pressure and feed tension, an interlocking density of 15 to 35 interlocking points / m can be obtained, ensuring both yarn evenness and subsequent weaving performance.

[0048] 7. Boiling water shrinkage rate

[0049] In this invention, the "boiling water shrinkage rate" refers to: taking the filament to be tested, straightening it under a specified pretension, and calibrating the initial gauge length between two points. Then, without external tension, the sample was completely immersed in boiling water at 100°C for 30 minutes, removed, allowed to cool naturally, and dried to constant weight under normal temperature and humidity conditions. Finally, the gauge length was measured. Its boiling water shrinkage rate is calculated using the following formula:

[0050]

[0051] in, To handle the front gauge length, The gauge length is the length after boiling water treatment and cooling and drying.

[0052] II. Formulation and Structural Mechanism of the Invention

[0053] The high-loft island-high-shrinkage polyester composite filament of the present invention mainly includes three design points at the formulation level: the dual-ocean phase structure of the island component, the ultra-fine control of the island phase, and the shrinkage performance and ratio matching of the high-shrinkage component filament.

[0054] 1. Dual marine design

[0055] This invention employs a dual-ocean-phase system where water-soluble PVA and alkali-soluble COPET coexist. The mass ratio of PVA to COPET is controlled at (30-60):(70-40), forming an interconnected or nested ocean-phase network at the spinning temperature. On one hand, PVA has high hydrophilicity and good hot water solubility, dissolving essentially within minutes in hot water at 90-98°C, providing a pathway for the selective dissolution and residue of COPET. On the other hand, COPET has a low Tg and high sensitivity to alkali solutions, allowing for gradual dissolution under mild alkali conditions. By controlling the PVA / COPET ratio, this invention ensures that PVA is preferentially dissolved and removed during the first-stage hot water treatment, while COPET maintains the basic stability of its island-island structure, preventing large-scale exposure or structural collapse of the island phase. During the second-stage mild alkali treatment, COPET gradually degenerates from a continuous phase to a discontinuous residue. Due to the difference in interfacial tension and dissolution kinetics between the PET island phase and the high-shrinkage polyester, it tends to accumulate at the circumferential interface of the high-shrinkage filament, ultimately forming a locally encapsulated structure.

[0056] 2. Sea / Island ratio and ultrafine island fiber

[0057] To achieve the delicate feel and high coverage required for applications such as suede and imitation wool, this invention preferably uses a mass ratio of marine phase to island phase in the island component of (25-40):(75-60), with the number of island filaments in the island phase PET being 24-64. If the marine phase ratio is too low, the fineness of the island filaments after weight reduction will be difficult to decrease to below 0.1 dtex, failing to form sufficiently fine pile; if the marine phase ratio is too high, structural instability and strength reduction are likely to occur during weight reduction. Within the above-mentioned marine / island ratio and number of island filaments, this invention, through reasonable selection of bus density and draw ratio, stably controls the linear density of the PET island phase filaments after weight reduction within the range of 0.03-0.10 dtex, achieving a comprehensive balance between spinnability, strength, and ultrafineness, providing a foundation for high-loft, high-coverage fabrics.

[0058] 3. High-shrinkage polyester formulation matched with linear density

[0059] The high-shrinkage component filament adopts a PTA / IPA / EG copolymer system, with the IPA molar fraction preferably being 8-18%. In preferred Examples 1 and 2, dicarboxylic acid monomers containing sulfonate hydrophilic groups are not introduced to ensure that the high-shrinkage polyester has similar crystallinity and alkali resistance to ordinary PET. In optional Example 3, a small amount of aromatic dicarboxylic acid monomers containing sulfonate hydrophilic groups can be introduced into the above system to further improve dyeability and hydrophilicity while maintaining shrinkage performance. Through formulation and drawing process control, the shrinkage rate of the obtained high-shrinkage filament in boiling water at 100°C is stabilized at 35-55%. This invention controls the linear density ratio of the island component filament to the high-shrinkage component filament at (40-70):(60-30). On the one hand, this ensures that the high-shrinkage component provides sufficient shrinkage driving force, enabling the composite filament to form a rich three-dimensional crimp structure during heat treatment and use; on the other hand, it avoids excessive high-shrinkage component, which would lead to an overly stiff fabric and a rough hand feel. After the reduction of the two-phase structure, the residual COPET mainly coats the circumferential direction of the high-shrinkage filament, binding several ultrafine island filaments and the high-shrinkage base into local "micro-units". During the external compression and shrinkage recovery process, the microstructure supports the excellent volume elasticity and cyclic compression recovery performance of the fabric of this invention.

[0060] This invention, through the synergistic design of the PVA / COPET dual-phase ratio, sea / island mass ratio, island number, and high-shrinkage polyester formulation and linear density ratio, constructs a composite skeleton structure in the fiber cross-section consisting of "ultra-fine PET island filaments, high-shrinkage polyester filaments, and circumferentially enriched COPET residual coating layer". This is the fundamental mechanism for achieving high bulkiness and high resilience under low alkali reduction conditions.

[0061] III. General Preparation Methods for Composite Filaments

[0062] The present invention provides a method for preparing high-loft island-type high-shrinkage polyester composite filament, which mainly includes raw material pretreatment, preparation of island-type pre-oriented yarn, preparation of high-shrinkage filament, composite drawing-heat setting-air interlacing, and hot water / light alkali segmented weight reduction, etc. There is a close process synergy between each step.

[0063] 1. Raw material pretreatment

[0064] PVA, COPET, PET, and high-shrinkage copolyester chips require thorough drying before extrusion to reduce the risk of hydrolysis and bubbling. Hot air drying at 120–140°C for 4–8 hours is typically used to control the moisture content below 50 ppm. For COPET or high-shrinkage copolyesters containing sulfonate monomers, the drying temperature should be appropriately reduced or the drying time shortened to avoid thermal degradation.

[0065] 2. Preparation of island-type pre-oriented POY yarn

[0066] PVA and COPET are mixed at a predetermined mass ratio, then melted separately and co-blended in a static mixer to obtain a homogeneous dual-phase melt. The melt temperature is generally controlled at 255–270°C to balance flowability and thermal stability. PET chips are melted in an extruder, with the melt temperature controlled at 270–285°C. The flow rates of the marine and island phase melts are precisely controlled using metering pumps to maintain the marine:island mass ratio within the range of 25–40:75–60, and the melt viscosity ratio is adjusted to 0.8–1.2 to ensure a stable marine / island interface and uniform island distribution during the spinning process.

[0067] Marine and island phase melts converge within the distribution plate and island-type spinneret assembly, and are extruded through a multi-hole spinneret to form a fiber stream with a predetermined number of islands. Downstream cooling is achieved using side-blowing air, with a preferred cooling air temperature of 18–24°C and a wind speed of 0.3–0.5 m / s to avoid excessively rapid cooling that could lead to cross-sectional shape deviations. After the fiber stream is coated with an appropriate amount of spinning oil by an oiling device, it is wound into POY at a winding speed of 2500–3500 m / min. Its bus density and single filament count are determined by a combination of the number of spinneret holes and the extrusion rate.

[0068] 3. Preparation of high-shrinkage component filaments

[0069] High-shrinkage copolyesters can be prepared using a conventional esterification-polymerization process. PTA and IPA are added in a molar ratio, EG is added for esterification, followed by polymerization under vacuum and high temperature conditions until the target intrinsic viscosity is reached. Appropriate amounts of terminators, stabilizers, and nucleating agents are added if necessary. After drying, the copolymer chips are spun into POY on a melt spinning machine at a melt temperature of 270–285°C and a winding speed of 2500–3200 m / min. Subsequently, through one or more stages of drawing, drawing and heat setting are performed on a hot plate or in a hot box at 140–190°C, with the total draw ratio controlled at 1.6–2.5, so that the resulting high-shrinkage filaments achieve a shrinkage rate of 35–55% in boiling water at 100°C, maintaining good strength and processing stability while meeting the high shrinkage requirements. To obtain a more uniform volumetric bulk structure and superior multiple compression recovery performance, this invention uses high-shrinkage yarns with a single yarn fineness of approximately 1.0 dtex, with a typical precursor yarn specification of 75 dtex / 72F. This specification has been widely used in the fields of high-shrinkage polyester, low-elasticity yarn and differentiated filaments. It is a conventional industrial product available in this field. Its spinning, drawing and weaving processes are mature and stable. Although it requires appropriate optimization of tension and oiling conditions compared to 30D / 12F or 75D / 36F, it does not increase the difficulty of implementing this invention. Those skilled in the art can obtain it in batches without creative labor.

[0070] 4. Composite drawing, heat setting and air bonding

[0071] Island-type pre-oriented yarn and high-shrinkage component filament are fed side-by-side into the drawing-heat-setting device at a linear density ratio of (40–70):(60–30). A total draw ratio of 1.6–2.5 is achieved by adjusting the front and rear roller speeds, and heat setting is performed in a hot box at 140–190°C to balance the orientation and crystalline structure of the island-type and high-shrinkage components. An air network nozzle is arranged at the drawing outlet to introduce compressed air at 0.2–0.5 MPa to form interlocking nodes, with a preferred interlocking node density of 15–35 nodes / m, ensuring good evenness and anti-separation ability of the composite filament. The winding speed is generally 800–1200 m / min and can be adjusted according to the target linear density and subsequent process requirements.

[0072] 5. Hot water removes PVA and reduces the amount of COPET dissolved by light alkali.

[0073] After unwinding, the composite filament package enters the first hot water bath under controllable tension. The hot water temperature is controlled at 90–98℃, and the treatment time is 1–10 minutes. The uniform dissolution of PVA is ensured by adjusting the bath ratio, circulation speed, and moderate stirring. After this stage, the mass loss is measured, which is generally 8–18%, mainly corresponding to the dissolution of PVA and a small amount of surface dissolution of COPET.

[0074] The filaments were then transferred to a second alkaline bath, with the NaOH concentration controlled at 1–5 g / L, the bath temperature maintained at 90–98°C, and the treatment time at 5–20 min. By controlling the alkali concentration and time, COPET underwent a limited degree of dissolution, increasing the overall weight reduction to 15–25%, but a certain amount of COPET remained. Since PVA was largely removed, the residual COPET was affected by the combined effects of interfacial energy and microflow during the dissolution process, gradually retreating from the central region and accumulating around the high-shrinkage filaments. This resulted in the composite fiber cross-section exhibiting a structure where ultrafine PET island filaments and high-shrinkage filaments were nested together, while a residual COPET band covered the outside of the high-shrinkage filaments.

[0075] After the weight reduction treatment, the filaments need to be thoroughly washed in multiple baths of warm water to remove residual alkali and dissolved substances until the pH of the effluent is close to neutral. Finally, they are dried under relaxation or slight tension conditions with hot air or hot plate at 120–150°C, and pre-cracking or pre-heat shrinkage treatment can be selected depending on the subsequent application. The composite filaments obtained by the above method exhibit excellent bulkiness, compression recovery, and durability in subsequent weaving, dyeing, and use.

[0076] IV. Examples

[0077] 1. Example 1: Preparation of a typical high-loft island-sea-high-shrinkage polyester composite filament

[0078] The raw materials used in this embodiment are as follows (by weight):

[0079] Table 1. Composition of island components and high-shrinkage components (Example 1)

[0080]

[0081] S1: Preparation of island-type pre-oriented yarns

[0082] Dried PVA and COPET chips were mixed at a mass ratio of 40:60, melted separately in extruders, and then co-blended in a static mixer to obtain a dual marine phase melt. The melt temperature was controlled at 255–265°C. Simultaneously, dried PET chips were melted in another melt extruder at a temperature controlled at 270–280°C. The screw speed and metering pump were adjusted to achieve a marine to island phase melt mass flow rate of 30:70, and the viscosity ratio of the marine to island phase melts was controlled at 0.9–1.1.

[0083] The dual-phase melt and PET melt are composite spun through the same island-type spinneret, with the spinneret island structure preset to 36 islands. The spinning temperature is controlled at 270℃, the side-blown cooling air temperature is 20℃, and the side-blown air velocity is 0.4m / s. After oiling and cooling, it is wound at a speed of 3000m / min to obtain island-type POY, with the following specifications:

[0084] Bus density: approximately 150 dtex;

[0085] Total monofilament count: 36F;

[0086] Number of "islands" in each filament: 36 islands.

[0087] At this point, each island filament contains 36 "islands" in the PET island phase and a PVA / COPET bicontinuous phase in the marine phase.

[0088] S2: Preparation of high-shrinkage copolyester filaments

[0089] Copolyester chips were prepared by esterification and polycondensation of PTA, IPA, and EG at a designed molar ratio. The IPA molar fraction was approximately 12%, and the intrinsic viscosity was approximately 0.64 dL / g. After drying, the chips were spun on a conventional melt spinning machine at a melt temperature controlled at 275℃ and a winding speed of 3000 m / min to obtain high-shrinkage copolyester POY. A one-step drawing process was then performed on a drawing machine with a total draw ratio of 2.0, followed by hot setting on hot plates at 80℃ for the first plate and 160℃ for the second plate, yielding high-shrinkage filaments with a specification of 75 dtex / 72F and a boiling water shrinkage rate of approximately 45% at 100℃.

[0090] S3: Composite drawing, heat setting and air bonding

[0091] The prepared island-type pre-oriented POY yarn and high-shrinkage polyester filament are drawn out from two sets of yarn frames and fed into the drafting and heat-setting device in parallel with a certain feeding tension.

[0092] The feed linear density of island-type yarn is approximately 150 dtex, while the feed linear density of high-shrinkage yarn is 75 dtex.

[0093] By adjusting the number of yarns, the linear density ratio of the island component filament to the high-shrinkage component filament is made to be 60:40.

[0094] The front roller speed of the drafting section is 600 m / min, the rear roller speed is 1200 m / min, and the total drafting ratio is approximately 2.0.

[0095] The temperature in the hot box is 170℃, and the dwell time is approximately 15 seconds.

[0096] An air network nozzle is installed at the drawing outlet, with compressed air pressure of 0.35 MPa, forming an interlacing node density of approximately 25 nodes / m. The final winding speed is approximately 1100 m / min, resulting in a composite filament bus density of approximately 125 dtex, and the fineness of each PET island filament is approximately 0.04 dtex.

[0097] S4: Hot water removes PVA, and light alkali reduces the amount of COPET partially dissolved.

[0098] The composite filaments were introduced into a 95°C hot water bath for 5 minutes in a relaxed state (tension ≤ 0.05 cN / dtex). A small amount of nonionic surfactant was added to the water bath to promote PVA dissolution. After treatment, the filaments were rinsed with warm water, dried, and weighed. The first mass loss was approximately 10.5%, indicating that the PVA in the marine phase was basically dissolved and removed.

[0099] Subsequently, the composite filaments were introduced into an alkaline bath containing 3 g / L NaOH, with the bath temperature controlled at 95℃ and the treatment time at 15 min. After treatment, the filaments were thoroughly washed with hot and cold water sequentially until neutral, dried, and weighed. The total mass loss was approximately 19.8%, and the alkali loss in the second stage was approximately 9.3%, indicating that the COPET in the marine phase was only partially dissolved.

[0100] The residual COPET no longer forms a continuous coating, but instead accumulates mainly in strips and blocks in the circumferential region near the high-shrinkage polyester filament, forming a local coating and bridging structure.

[0101] Example 2: Composite filaments with varying PVA / COPET ratios

[0102] This embodiment is basically the same as Embodiment 1, except that the mass ratio of PVA to COPET is adjusted to 30:70, and the mass ratio of marine phase to island phase remains at 30:70.

[0103] Steps S1 to S4 of Example 1 were repeated, with the hot water treatment time adjusted to 6 minutes, the NaOH concentration maintained at 3 g / L, and the treatment time 15 minutes. Test results showed that the first mass loss was approximately 9.2%, the total mass loss was approximately 18.6%, the PET island filament fineness was approximately 0.04 dtex, and the total amount of residual COPET was slightly higher than in Example 1, but it was still mainly distributed in the circumferential coverage area of ​​the high-shrinkage filament. The overall bulkiness and resilience of the composite filament were basically the same as in Example 1, and the fabric weight was slightly lower.

[0104] Example 3: Introduction of sulfonate comonomers into high-shrinkage copolyesters

[0105] This embodiment is based on Example 1, and modifies the high-shrinkage copolyester by introducing a small amount of aromatic dicarboxylic acid containing sulfonate hydrophilic groups to improve dyeability and hydrophilicity. At the same time, the effect on fluffiness and resilience is investigated.

[0106] The high-shrinkage copolyester formulation is: PTA / IPA / 5-SIP-Na / EG, wherein the molar fraction of IPA is approximately 12% and the molar fraction of 5-SIP-Na is approximately 0.8%.

[0107] Copolyester chips were prepared and spun and drawn according to the conditions of Example 1 to obtain high-shrinkage filaments of 75 dtex / 72f with a shrinkage rate of about 43% when boiling water at 100°C.

[0108] The island-island yarn was prepared according to the conditions of Example 1 (PVA:COPET=40:60, sea:island=30:70, 150 dtex / 36F, 36 islands), with a composite ratio of 60:40 and a bus density of approximately 125 dtex;

[0109] The conditions for reducing the amount of hot water and light alkali are the same as in Example 1.

[0110] V. Comparative Examples

[0111] The specifications of the island-type POY and high-shrinkage yarn in the comparative example are the same as those in the example.

[0112] Comparative Example 1: Single COPET marine island-high shrinkage composite filament (traditional strong alkali reduction)

[0113] Comparative Example 1 uses traditional single COPET marine island fiber, which is compounded with the high shrinkage copolyester filament of Example 1, and the other conditions are basically the same.

[0114] 1) Island composition: The marine phase is COPET (excluding PVA), the island phase is PET, the marine:island mass ratio is 30:70, and the number of islands is 36;

[0115] 2) The spinning, drawing, and interlacing conditions are the same as in Example 1;

[0116] 3) Reduced fiber opening adopts conventional strong alkali process: NaOH concentration 20g / L, temperature 98℃, treatment time 40min, tension controlled below 0.05cN / dtex, followed by water washing and drying.

[0117] Comparative Example 2: Single PVA marine island-high shrinkage composite filament (hot water treatment only)

[0118] Comparative Example 2 uses single PVA marine island fiber, which is composited with the high shrinkage copolyester filament of Example 1, with other conditions being basically the same.

[0119] 1) Island composition: marine phase is PVA, island phase is PET, marine:island mass ratio is 30:70, number of islands is 36;

[0120] 2) The spinning, drawing, and interlacing conditions are the same as in Example 1;

[0121] 3) The weight reduction treatment only used 95℃ hot water for 10 minutes, without the use of alkali for weight reduction. PVA was basically completely dissolved, and the fineness of PET island fibers was about 0.04 dtex.

[0122] VI. Performance Testing Methods and Results

[0123] 1. Testing Method

[0124] 1) Linear density and single filament fineness

[0125] The total density of the filament is determined according to GB / T 14343, and the fineness of the filament is calculated in combination with the number of filaments.

[0126] 2) Boiling water shrinkage rate

[0127] According to GB / T 6505, the length change is calculated after treatment in boiling water at 100℃ for 30 minutes, followed by cooling and drying.

[0128] 3) Fracture strength and elongation at break

[0129] The measurement was performed according to GB / T 14344, using the fixed-length method.

[0130] 4) Fabric preparation, weight, and thickness

[0131] The composite filaments of each embodiment and comparative example were made into warp-knitted suede fabrics with the same structure. They were then subjected to conventional napping and shearing, and conditioned at 20°C and 65% RH for 24 hours. The basis weight and initial thickness were measured using an electronic balance and a thickness gauge.

[0132] 5) Compression recovery performance

[0133] The fabric was compressed under 5 kPa pressure for 1 minute, and the thickness was measured 1 minute after release. The compression recovery rate was calculated once. Then, 10,000 and 20,000 cycles of compression tests were performed, and the corresponding thickness recovery rates were calculated.

[0134] 6) Evaluation of volumetric elasticity

[0135] The volumetric elasticity index is calculated by integrating the area of ​​the loading-unloading curve using a standardized method. A higher index indicates better volumetric elasticity.

[0136] 2. Comparison of fiber structure and weight reduction parameters

[0137] A comparison of composite filament weight reduction processes is shown in Table 2.

[0138] Table 2 Comparison of Composite Filament Weight Reduction Process and Structural Parameters

[0139]

[0140] As can be seen from Table 2, the embodiments of the present invention achieved a total mass reduction similar to or even slightly lower than that of Comparative Example 1 at a lower NaOH concentration (3 g / L) and a shorter treatment time (15 min). At the same time, a COPET residual coating area close to the circumferential direction of the high shrinkage filament was formed on the fiber cross-section. In contrast, Comparative Example 1 used a strong alkali with a NaOH concentration of 20 g / L for mass reduction, which completely dissolved the marine phase and made the PET island filament surface easy to be etched.

[0141] 3. Mechanical and shrinkage properties

[0142] The mechanical properties of the composite filaments are shown in Table 3.

[0143] Table 3 Comparison of Mechanical Properties and Shrinkage Rate of Composite Filaments

[0144]

[0145] As shown in Table 3, compared with Comparative Example 1, Examples 1-3 all showed varying degrees of improvement in breaking strength and elongation at break, indicating that using low-concentration NaOH for partial weight reduction causes less damage to the PET island filaments and is beneficial for maintaining the overall mechanical properties of the filaments. Although Comparative Example 2 was also not treated with alkali and had high strength, its structure lacked the support of the residual COPET skeleton, resulting in insufficient bulk elasticity and compression recovery of the subsequent fabric.

[0146] 4. Fabric bulkiness and compression recovery properties

[0147] The composite filaments were spun into suede fabrics with the same structure, and the finishing conditions were uniform. The test results are shown in Table 4.

[0148] Table 4 Comparison of Fabric Weight, Thickness, and Compression Recovery Performance

[0149]

[0150] As shown in Table 4, under similar thickness conditions, the fabric weight of Examples 1-3 of the present invention is lower than that of Comparative Example 1, indicating that a certain degree of lightweighting is achieved under the same volumetric feel. At the same time, the thickness recovery rate after 10,000 and 20,000 compression cycles is significantly higher than that of Comparative Example 1 and Comparative Example 2, and the volumetric elasticity index is also significantly higher, indicating that the residual COPET coating structure formed by the dual marine phase and segmented dissolution effectively improves the long-term compression recovery performance and volumetric elasticity of the fabric.

[0151] In Comparative Example 1, due to the complete dissolution of COPET by strong alkali, the PET island filaments were severely etched, and the fabric underwent irreversible compaction after multiple compressions, resulting in a significant decrease in recovery rate. In Comparative Example 2, although the PET island filaments remained intact, due to the complete dissolution of the marine phase and the absence of residual COPET skeleton, the high-shrinkage fibers shrank, causing some of the ultrafine island filaments to become severely entangled and collapsed. Under long-term compression, it was difficult to maintain a high-loft structure.

[0152] The comparison between the above embodiments and comparative examples shows that:

[0153] a. This invention achieves selective dissolution of the marine phase by adopting a PVA / COPET dual marine phase structure and using a segmented reduction process of "hot water and light alkali" at low NaOH concentration and short treatment time. PVA is completely dissolved and COPET is only partially dissolved, which significantly reduces the etching of PET island filaments by strong alkali. The breaking strength and breaking elongation of the filaments are better than those of Comparative Example 1, which completely dissolves COPET with strong alkali.

[0154] b. Since the COPET residue is mainly concentrated in the circumferential coverage area of ​​the high-shrinkage component filament, during subsequent weaving, heat shrinking and use, the residual COPET acts as a flexible skeleton to form a synergistic deformation unit with the high-shrinkage filament and ultrafine island yarn, effectively dispersing the compression load and improving the fabric's volume elasticity and cyclic compression recovery ability.

[0155] c. Compared with Comparative Example 2, which uses a single PVA sea phase, this invention, while having a similar fineness of ultra-fine island yarn, constructs a more stable three-dimensional support system through residual COPET, which significantly improves the bulkiness and long-term thickness retention of the fabric under similar or lower basis weight conditions.

[0156] Therefore, the technical solution of the present invention not only reduces the alkali reduction intensity and environmental burden in the process, but also achieves synergistic optimization between PVA / COPET dual marine phase, PET island yarn and high shrinkage fiber in structural design. It achieves a good balance between the lightweight of high-loft fabric and high durability compression recovery, and achieves a comprehensive effect that is difficult to achieve with existing technologies.

[0157] Those skilled in the art should understand that the specific embodiments, examples, and comparative examples described above are merely for further illustrating the formulation design concept, structural mechanism, and process implementation path of the present invention, and are intended to intuitively demonstrate the comprehensive technical effects achieved by the present invention compared to the prior art in terms of weight reduction conditions, fiber structure, and fabric bulkiness and compression recovery. They do not constitute a limitation on the scope of protection of the present invention. Without departing from the core concept of the present invention, reasonable modifications such as substitution of component raw materials, numerical fine-tuning, or changes in the process sequence can achieve technical effects similar to those described in this specification. All equivalent transformations or combinations made based on the claims of the present invention should fall within the scope of protection of the present invention.

Claims

1. A high-loft island-sea-high-shrinkage polyester composite filament, characterized in that, This composite filament is composed of a sea-island component filament and a high-shrinkage component filament: The island-type filament is an island-type polyester filament, the sea phase is water-soluble PVA and alkali-soluble COPET, the mass ratio of PVA to COPET is (30-60):(70-40); the island phase is PET. The high-shrinkage component filament is a copolyester filament with a boiling water shrinkage rate of 35-55%. The linear density ratio of the island component filament to the high-shrinkage component filament is (40-70):(60-30). The composite filament is subjected to hot water treatment at 90-98℃ and alkaline reduction treatment with 1-5g / L sodium hydroxide aqueous solution to dissolve and remove PVA in the marine phase and partially dissolve COPET. The linear density of the PET island phase monofilament in the resulting composite filament is 0.03-0.10dtex, and the residual COPET is mainly distributed in the circumferential coating area close to the high-shrinkage component filament.

2. The composite filament according to claim 1, characterized in that, The mass ratio of marine phase to island phase in the filaments of the island component is (25-40):(75-60), and the number of islands in the PET island phase monofilaments is 24-64.

3. The composite filament according to claim 1, characterized in that, The PVA has a saponification degree of 88-99% and a number-average degree of polymerization of 800-2000.

4. The composite filament according to claim 1, characterized in that, The COPET is copolymerized from terephthalic acid, ethylene glycol, and aromatic dicarboxylic acids containing sulfonate hydrophilic groups, and its glass transition temperature is 10-30°C lower than that of PET.

5. The composite filament according to claim 1, characterized in that, The high-shrinkage component filament copolyester is obtained by copolymerizing terephthalic acid, isophthalic acid and ethylene glycol, wherein the molar fraction of isophthalic acid is 8-18%.

6. A method for preparing the high-loft island-sea-high-shrinkage polyester composite filament according to any one of claims 1 to 5, characterized in that, include: S1, PVA and COPET are melt-blended to obtain a dual marine phase melt, which is then spun into a sea-island type composite melt in the same spinneret as the PET melt to obtain a sea-island type pre-oriented yarn POY with PVA / COPET as the marine phase and PET as the island phase; S2, prepare copolyester and perform melt spinning and drawing to obtain high shrinkage component filaments with a boiling water shrinkage rate of 35-55%; S3, the island-type pre-oriented yarn and the high-shrinkage component filament are fed into the drawing and heat-setting device in parallel at a linear density ratio of (40-70):(60-30), drawn at a total drawing ratio of 1.6-2.5, and heat-set in a hot box at 140-190°C. At the same time, they are bundled together through an air network nozzle to obtain composite filament. S4. The composite filament is treated in hot water at 90-98°C for 1-10 minutes to dissolve and remove PVA from the marine phase, and then treated in a 1-5 g / L sodium hydroxide aqueous solution for 5-20 minutes to partially dissolve COPET from the marine phase. It is then washed with water and subjected to relaxation heat treatment.

7. The method according to claim 6, characterized in that, In step S1, the spinning temperature of the island-type POY is 260-290℃, the cooling air temperature is 18-24℃, the winding speed is 2500-3500m / min, and the viscosity ratio of the marine melt to the island melt is 0.8-1.

2.

8. The method according to claim 6, characterized in that, In step S3, the overfeed rate of the high-shrinkage component filament relative to the island component filament is 5-15%, the air pressure of the air network nozzle is 0.2-0.5 MPa, and the cross-link density of the resulting composite filament is 15-35 nodes / m.

9. The method according to claim 6, characterized in that, After the hot water treatment in step S4, the mass reduction of the composite filament is 8-18%, and after the alkali reduction treatment, the total mass reduction of the composite filament is 15-25%.

10. The use of the high-loft island-high-shrinkage polyester composite filament according to any one of claims 1 to 5, characterized in that, Used to prepare suede, imitation wool, or high-loft filling materials.

Citation Information

Patent Citations

  • Process for producing wool-like polyester composite filament yarn

    CN100595358C

  • Sea-island composite fiber and superfine fiber fabric

    CN103122502A

  • Superfine fiber composite filter material and preparation method thereof

    CN116328425A

  • Preparation method of soft artificial leather

    CN118910897A